2023
DOI: 10.1371/journal.ppat.1011261
|View full text |Cite
|
Sign up to set email alerts
|

The claudin-like apicomplexan microneme protein is required for gliding motility and infectivity of Plasmodium sporozoites

Abstract: Invasion of host cells by apicomplexan parasites such as Toxoplasma and Plasmodium spp requires the sequential secretion of the parasite apical organelles, the micronemes and the rhoptries. The claudin-like apicomplexan microneme protein (CLAMP) is a conserved protein that plays an essential role during invasion by Toxoplasma gondii tachyzoites and in Plasmodium falciparum asexual blood stages. CLAMP is also expressed in Plasmodium sporozoites, the mosquito-transmitted forms of the malaria parasite, but its ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…This enabled the first genome‐wide CRISPR/Cas9 loss‐of‐function screen in Toxoplasma , identifying fitness‐conferring genes critical for invasion of the host cell, including clamp (claudin‐like Apicomplexan microneme protein) (Table 1). Phenotypic validation studies confirmed CLAMP's importance in Toxoplasma invasion and the P. falciparum lytic cycle as well as in sporozoites (Loubens et al., 2023).…”
Section: Crispr/cas Knock‐out Screens: a Powerful Approach For Forwar...mentioning
confidence: 79%
“…This enabled the first genome‐wide CRISPR/Cas9 loss‐of‐function screen in Toxoplasma , identifying fitness‐conferring genes critical for invasion of the host cell, including clamp (claudin‐like Apicomplexan microneme protein) (Table 1). Phenotypic validation studies confirmed CLAMP's importance in Toxoplasma invasion and the P. falciparum lytic cycle as well as in sporozoites (Loubens et al., 2023).…”
Section: Crispr/cas Knock‐out Screens: a Powerful Approach For Forwar...mentioning
confidence: 79%
“…Investigating the three mutants we found that all formed similar numbers of sporozoites in oocysts and that all could colonize the salivary glands to similar levels (Figure 2C). Sporozoites move at high speeds and thus deletion of genes often affects their gliding motility (43,(46)(47)(48). To investigate gliding activity, we allowed salivary gland derived sporozoites to settle on a glass substrate and imaged their movement.…”
Section: Resultsmentioning
confidence: 99%
“…An infection is initiated when a female Anopheline mosquito infected with the parasite inoculates an estimated 15–123 sporozoites under the skin of an individual while probing for a blood vessel to take a meal [ 16 , 17 , 18 , 19 , 20 ]. While under the skin, the sporozoites get activated based on the environmental milieu, express proteins required for gliding motility and cell traversal and travel through the blood to the liver using the sinusoids as entry points to hepatocytes [ 21 , 22 , 23 , 24 ]. The sinusoids are lined with resident macrophages, the Kupffer cells that aid in the transmigration of the sporozoites via gliding motility [ 25 ] through the sinusoids to reach hepatocytes [ 26 , 27 ].…”
Section: Life Cycle Of Human Plasmodium Parasites ...mentioning
confidence: 99%